2020
DOI: 10.3390/jmse8080579
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Assimilated Coastal Wave Data in the Northwestern Pacific Area

Abstract: The assimilated coastal wave data are useful for wave climate study, coastal engineering, and design for marine disaster protection. However, the assimilated coastal wave data are few. Here, wave analysis data produced by the JMA (Japan Meteorological Agency) and ERA5 wave data were compared with GPS (Global Positioning System) buoy-measured wave data. In addition, the accuracy of ERA5 wave data for various conditions was investigated. The accuracy of JMA analysis wave height was better than that of ERA5 wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The accuracy of the ERA5 wave data was verified by Reference [10], which shows the good accuracy. If it is verified that the drifting buoy wave data is more accurate than the ERA5 wave data, it can be shown that the drifting buoy wave data is useful for verification of the wave prediction data.…”
Section: Introductionmentioning
confidence: 80%
“…The accuracy of the ERA5 wave data was verified by Reference [10], which shows the good accuracy. If it is verified that the drifting buoy wave data is more accurate than the ERA5 wave data, it can be shown that the drifting buoy wave data is useful for verification of the wave prediction data.…”
Section: Introductionmentioning
confidence: 80%
“…From that study it was revealed that the ERA5 swell wave heights were overestimated during monsoon and post-monsoon seasons, while wind wave heights were not accurate for the monsoon period (RMSE = 0.32 m). On the other hand, Hisaki [37] evaluated ERA5 wave height data with wave measurements from buoys at 18 coastal locations around Japan and concluded that ERA5 wave height tends to be underestimated for increasing wave heights.…”
Section: Descriptionmentioning
confidence: 99%
“…Thus, using data on pressure on the ocean floor observed from the sensors (S-net), a method for estimating tsunamis in almost real-time mode was developed [10]. JMA has an enormous seismic and metrological database, used by many scientists for various studies unrelated to forecasting and estimating the impact of tsunamis [11,12]. Based on JMA data, a seismic method was developed for use in tsunami warning that is based on the detection of the W-phase that appears between P-waves and S-waves in seismic records.…”
Section: Introductionmentioning
confidence: 99%